INTERPRETING CARBON-ISOTOPE EXCURSIONS: CARBONATES AND ORGANIC MATTER - Kump L.R.; Arthur M.A. (My University, 1999)
Variations in the carbon isotopic compositions of marine carbonate and organic carbon provide a record of changes in the fraction of organic carbon buried through time and may provide clues to changes in rates of weathering and sources of organic carbon. Paired carbonate and organic carbon isotope determinations provide a possibility of interpreting not only changes in the global carbon cycle through time, but changes in atmospheric pCO2 as well. Interpretations of these types of data are typically rather qualitative; a quantitative basis is required to develop a better understanding of changes in the carbon cycle. For this purpose, we employ a simple model of the global carbon cycle which is subjected to a number of different perturbations, each lasting 500 ky, i.e., much longer than the residence times of carbon and phosphorus in the ocean-atmosphere system. In addition to standard considerations of carbon mass and isotopic fluxes to the ocean-atmosphere system from weathering and volcanism and fluxes of organic carbon and carbonate-carbon to sediments, the model incorporates sensitivity of the photosynthetic carbon isotope effect to changes in pCO2. The inclusion of this parameter leads to unexpected carbon isotope responses to forcing that causes increased rates of organic carbon burial. A series of simple to more complex simulations illustrates the significant effects of varying differences between the carbon isotopic composition of sedimented carbonate and organic carbon (ΔB). With constant ΔB a 50% increase in organic carbon burial produces a parallel increase in carbonate and organic carbon isotopic compositions. However, the same simulation with ΔB responsive to pCO2 changes produces an initial parallel δ13C increase, but this is followed by an even greater 13C-enrichment in organic carbon because pCO2 falls in response to increased organic carbon burial. The counterintuitive overall result of the enhanced organic carbon burial event is that the carbonate carbon isotopic composition actually decreases because of the more substantial increase in δ13Corg. In addition, we illustrate the effects on carbon isotopic compositions of the oceanic inorganic carbon reservoir and buried organic matter of a 50% increase in volcanic CO2 outgassing, a 50% increase in weathering rate (with coupled phosphate and riverine carbon flux responses), a 50% decrease in shale-associated organic carbon weathering, a 50% decrease in silicate weathering rate, and the possible effects of the rise in abundance of C4 plants in the late Miocene to Recent. We compare the model simulated carbon isotopic responses for some of these experiments to paired carbonate- and organic-carbon records to illustrate how these records might be interpreted in light of the model response.
Keywords: CARBON-13; ISOTOPE EXCURSIONS; MODELING; BIOGEOCHEMICAL CYCLES; ORGANIC CARBON; MARINE GEOCHEMISTRY